Effect of starter cultures on the quality of Suan yu, a Chinese traditional fermented freshwater fish. (21st June 2016) - Zeng, Xuefeng; Zhang, Wei; Zhu, Qiujin
Summary: The generation of volatile compounds of four starter cultures composed of isolated microorganisms from traditional Suan yu was investigated. The cultures included two pure starters (PS1: Lactobacillus plantarum 120 and PS2: Pediococcus pentosaceus 220 ) and two mixed starters (MS1: L. plantarum 120, Staphylococcus xylosus 135 and Saccharomyces cerevisiae 31 at 1:1:1; MS2: P. pentosaceus 220, S. xylosus 135 and S. cerevisiae 31 at 1:1:1). Naturally fermented Suan yu was used as control. The volatile compounds were collected from the headspace of the samples by Solid‐phase microextraction and analysed by gas chromatography–mass spectrometry. The type and total content of volatile compounds in the mixed‐starter‐fermented fish were higher than those of the pure‐starter‐fermented samples and control. A total of seventy nine and eighty volatile compounds were detected in Suan yu fermented with MS1 and MS2, respectively, with ethanol as the predominant compound and hexanal, ethyl acetate, 3‐methylbutanol, 3‐hydroxy‐2‐butanone, hexanoic acid ethyl ester and 2, 3‐butanedione as the other compounds. Furthermore, the sensorial acceptance of the different products with mixed starter cultures seemed to improve the quality of Suan yu products. Abstract : Relationships among fermented 'suan yu' inoculated with different starter cultures (PS1, PS2, MS1, MS2) and the control batch and volatile compounds obtained by principal component analysis (PCA). Higher scores were obtained through the majority of attributes analysed in the batches with mixed starter cultures, and this was related to ethanol, 3‐methylbutanol, 1‐hexanol, hexanal, 3‐hydroxy‐2‐butanone, 2‐octen‐1‐ol, ethyl acetate, hexanoicaci dethyl ester, octanal, nonanal and 2‐methyl butanoic acid‐ethyl ester levels, which were main compounds in Suan yu samples inoculated with mixed starter cultures and might be contributed to a positive effect on final flavour.